Amniotic Membrane Transplantation in Ophthalmology: An Updated Perspective - Walkden A (Dove Medical Press, 2020)
Andrew Walkden1,2 1Manchester Royal Eye Hospital, Manchester University Foundation Trust, Manchester, UK; 2University of Manchester Faculty of Medical and Human Sciences, Manchester, Greater Manchester, UKCorrespondence: Andrew Walkden Email walkdenandrew@gmail.comAim: The aim of this paper is to provide a succinct literature review of the different clinical applications for AMT usage in an ophthalmic setting, ranging from commonly used applications to less mainstream approaches. The hope is that this review enables the reader to have a better understanding of the biological properties of amnion as well as the indications and scenarios in which AMT can be used, whilst presenting relevant evidence from within the literature which may be of interest. We also provide an update on the methods of preservation of amniotic membrane and the application methodologies.Methods: Literature search. A PubMed search was performed using the search terms “amniotic membrane transplant”, “amnion AND cornea”, amnion AND ophthalmology”, “amnion AND ocular surface” and “Amnion AND eye”. A full review of the literature using the PubMed database was conducted up until 01/05/20. The articles used were written in English, with all articles accessed in full. Both review articles and original articles were used for this review. All full publications related to ophthalmology were considered.Keywords: amnion, amniotic membrane transplant, amniotic membrane graft, amniotic membrane